Productivity at the workstation : maintaining fitness at your desk - Dvorak, Robert Regis (Crisp Pub. Los AltosUS, 1990)
Provides many suggestions for workers who must spend hours at a desk or workstation with a typewriter or Visual Display Terminal. Aims to make workers aware of their environment and teach them how to care their bodies so they can work more comfortably and productively. Addresses areas including: exercise, movement, diet, sleep, posture, work habits, vision care, and mental balance.